2015
DOI: 10.1097/prs.0000000000000971
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to Support Controversy in Microsurgery

Abstract: Microsurgery practice, including preoperative patient selection, intraoperative technique, and anesthetic considerations, varies from institution to institution and from surgeon to surgeon. Many surgeons' practices are driven by "conventional wisdom," which is handed down from mentors to fellows and residents. In this article, the authors explore the oxymoron that there is evidence to support controversy in microsurgery. Indeed, if there was convincing evidence to support varying microsurgery practices, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 195 publications
(213 reference statements)
2
21
0
Order By: Relevance
“…Similarly, Coskunfirat et al () demonstrated a strong association of ASA classification with the risk of adverse medical events. BMI also demonstrated statistically significant association with surgical complications, consistent with the consensus in the literature (Fan et al, ). However, as 34% of the US population is classified as obese, obesity should not be considered an absolute contraindication, but rather these patients should be optimized preoperatively (Fan et al, ; Mitchell, Catenacci, Wyatt, & Hill, ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similarly, Coskunfirat et al () demonstrated a strong association of ASA classification with the risk of adverse medical events. BMI also demonstrated statistically significant association with surgical complications, consistent with the consensus in the literature (Fan et al, ). However, as 34% of the US population is classified as obese, obesity should not be considered an absolute contraindication, but rather these patients should be optimized preoperatively (Fan et al, ; Mitchell, Catenacci, Wyatt, & Hill, ).…”
Section: Discussionsupporting
confidence: 89%
“…BMI also demonstrated statistically significant association with surgical complications, consistent with the consensus in the literature (Fan et al, ). However, as 34% of the US population is classified as obese, obesity should not be considered an absolute contraindication, but rather these patients should be optimized preoperatively (Fan et al, ; Mitchell, Catenacci, Wyatt, & Hill, ). Longer operative times were associated with surgical complications, and longer hospital length of stay was associated with both surgical and medical complications.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…25 A recent review by Fan et al concluded that there are insufficient data to refute this evidence. 42 A recent meta-analysis evaluating the efficacy of thromboprophylactic agents used in microsurgery concluded that HSQ reduced the risk of flap loss by 35% but raised the risk of hematoma, though these differences were significant. 30 In a retrospective review of 470 patients undergoing free tissue transfer, HSQ was found to be a safe agent that did not increase the risk of postoperative bleeding, hematoma, or flap failure.…”
Section: Subcutaneous Heparinmentioning
confidence: 99%